(untitled) (Revista Latino-Americana de Enfermagem, 2024)
Objective: to investigate the relationship between team climate and job satisfaction among professionals working in mobile pre-hospital care. Method: this is a quantitative, correlational study carried out in a mobile pre-hospital care service in the São Paulo Metropolitan Region. The participants were 95 professionals, allocated to 40 teams, who answered three questionnaires: sociodemographic/labor data, Team Climate Scale and S20/23 Job Satisfaction Scale. Descriptive statistics and multilevel linear models were used for the analysis, including moderation effects. The Backward method was used to ascertain the order of significance. Results: in the models, the relationships between satisfaction with hierarchical relationships and the factor “support for new ideas” moderated for men and “task orientation” for women were significant. For satisfaction with the physical environment, “working hours” and “participation in the team” were significant and, for intrinsic satisfaction, the regime, working hours and the factors “team objectives”, “participation in the team” and “support for new ideas” remained significant, as did the moderation effect between length of service, “participation in the team” and “support for new ideas”. Conclusion: team climate is influenced by job satisfaction in a heterogeneous way and the moderating effect of this relationship is associated with gender and length of service.